Problem popularizacije strokovnih besedil - Uršič, Matjaž (Urbani izziv, 2008)
In the period after the post-socialist transition of Slovenia we can notice anincreased number of instrumental, marketing oriented public relation (PR) activities in expert and popular media from the field of spatial planning. The problem of instrumentalisation of media discourses reflects in exclusion i.e. deficiency of content-argumentative language in public debate. The basic purpose of the article is to analyse and expose some of the relationships and processes that have great influence in the space of the city and its surroundings. The article draws on empirical evidence from quantitative and qualitative analyse of texts and pays attention to some of the actual cases inspatial planning that show hidden contents, explicit and implicit ideological constructions, particularisms of interest groups and strategies of instrumental marketing campaigns.
Keywords: Ljubljana; mass media; množični mediji; prostorski razvoj; prostorsko planiranje; spatial planning; strokovni časopisi; strokovni sestavki; urbanism; urbanistično planiranje; urbanizem